JEJAK SEJARAH KERAJAAN NAGE - Wona, Maria Y.; Rema, Fransiskus X. (Program Studi Pendidikan Sejarah Universitas Flores, 2020)
After the Dutch took control of Nage, this system of government then changed to follow the policy of the Dutch who formed a new system called the Zelfbestuurende Landschap which was led by Bestuurder who was a King. The leadership structure under the king was the Hamente who was appointed by the Dutch and the Village Head who was appointed by the Hamente Head who came from the aristocrats from the swapraja area. Swapraja region is a region that has the right of self-government known as Zelfbestuur during the Dutch colonial period, this region is a form recognized by the Dutch. The status of this area states that the area is led by an indigenous leader who has the right to regulate administrative affairs, law and internal culture. In the period 1912 to 1917, the Netherlands formed 6 Landschap Bestuur in the Ngada region, one of which was: Nage was led by Roga Ngole. Landschap Bestuur Nage is the essence of this writing, Nage which in the Roga Ngole government there are many changes, both in a more organized social system that has only one leader, namely the King formed by the Netherlands so that all things related to the customary law system and all events in the kingdom can be governed by King. As for the new government structure, the Netherlands, namely the King, was assisted by the Head of Hamente / Head of Mere, the Head of the Village who was appointed by Hamente, and the last was Opas who became the king's arm.